(untitled) (Global Journal of Human-Social Science, 2021)
The competency-based approach meant the incorporation into the educational system of a repeated demand received regarding the adaptation of school work to the real needs of the students’ environment through active methods. The task-based approach is the application of the competencybased perspective in a linguistic subject. After implementing the task-based approach and through reflective practice, the learning achieved was evaluated to check whether the results of the same show differences in relation to socio-demographic variables. Based on a quasi-experimental design, a control group and an experimental group of 124 secondary school students were used. An evaluation instrument was designed and validated for data collection. The results of the research presented here show to what extent the socio-demographic variables of the students have been determining factors in their level of learning achieved in the language proficiency factors studied.